The development and application of cultural archetypes for understanding innovation capability - Sahota, Parminder Singh (Cranfield University, 2002)
This thesis recognizes that organizational culture is a primary determinant of innovation capability and argues the need to better understand this relationship or process as a necessary prerequisite to nurturing it in a more structured and systematic manner. The study explores this relationship within an R&D environment in telecommunications. It draws upon the knowledge management, organisational behaviour and organisational theory literatures to conceptualise organisational culture as a repository of knowledge. Using a soft systems bottom up approach four cultural archetypes with specific knowledge dynamics are identified and developed through a three-phase multi-method research strategy. These provide a clearer understanding of the relationship between organisational culture and innovation capability. The thesis concludes by considering strategies for improving innovation capability through the effective and appropriate movement between these archetypes.
Keywords: innovation capability; organisational culture; telecommunications